2018
DOI: 10.1242/jeb.181347
|View full text |Cite
|
Sign up to set email alerts
|

Active touch in sea otters: in-air and underwater texture discrimination thresholds and behavioral strategies for paws and vibrissae

Abstract: Sea otters () are marine predators that forage on a wide array of cryptic, benthic invertebrates. Observational studies and anatomical investigations of the sea otter somatosensory cortex suggest that touch is an important sense for detecting and capturing prey. Sea otters have two well-developed tactile structures: front paws and facial vibrissae. In this study, we use a two-alternative forced choice paradigm to investigate tactile sensitivity of a sea otter subject's paws and vibrissae, both in air and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 82 publications
3
17
0
Order By: Relevance
“…The discrimination of textures on these different spatial scales involve different neural coding mechanisms, the specifics of which depend on features of any given tactile sensory apparatus -these include the spacing of peripheral receptors, the size of their receptive fields, as well as active touch strategies used (Diamond et al, 2010;Grant et al, 2013). Coarse texture discrimination has been described in a number of mammals that rely on texture for important sensory mediated behaviors using a variety of body parts such as the fingertips in humans (Lamb, 1983;Morley et al, 1983) and non-human primates (squirrel monkey - Hille et al, 2001), the trunk in elephants (Dehnhardt et al, 1997), the forepaws and whiskers in sea otters (Strobel et al, 2018), and the whiskers in harbor seals (Dehnhardt et al, 1998), sea lions (Dehnhardt, 1994;Dehnhardt and Dücker, 1996), manatees (Bachteler and Dehnhardt, 1999;Bauer et al, 2012), and laboratory rodents (Carvell and Simons, 1990). However, fine texture discrimination (Diamond 2010), has only been extensively characterized for the whisker system in laboratory rodents and fingertips in primates (Connor et al, 1990;Connor and Johnson, 1992;Arabzadeh et al, 2005;Hollins and Bensmaia, 2007;von Heimendahl et al, 2007;Wolfe et al, 2008;Diamond 2010;Jadhav and Feldman, 2010;Pacchiarini et al, 2017).…”
Section: Fine Texture Discrimination In Mammalsmentioning
confidence: 99%
“…The discrimination of textures on these different spatial scales involve different neural coding mechanisms, the specifics of which depend on features of any given tactile sensory apparatus -these include the spacing of peripheral receptors, the size of their receptive fields, as well as active touch strategies used (Diamond et al, 2010;Grant et al, 2013). Coarse texture discrimination has been described in a number of mammals that rely on texture for important sensory mediated behaviors using a variety of body parts such as the fingertips in humans (Lamb, 1983;Morley et al, 1983) and non-human primates (squirrel monkey - Hille et al, 2001), the trunk in elephants (Dehnhardt et al, 1997), the forepaws and whiskers in sea otters (Strobel et al, 2018), and the whiskers in harbor seals (Dehnhardt et al, 1998), sea lions (Dehnhardt, 1994;Dehnhardt and Dücker, 1996), manatees (Bachteler and Dehnhardt, 1999;Bauer et al, 2012), and laboratory rodents (Carvell and Simons, 1990). However, fine texture discrimination (Diamond 2010), has only been extensively characterized for the whisker system in laboratory rodents and fingertips in primates (Connor et al, 1990;Connor and Johnson, 1992;Arabzadeh et al, 2005;Hollins and Bensmaia, 2007;von Heimendahl et al, 2007;Wolfe et al, 2008;Diamond 2010;Jadhav and Feldman, 2010;Pacchiarini et al, 2017).…”
Section: Fine Texture Discrimination In Mammalsmentioning
confidence: 99%
“…The research of Marshall et al (2014) supported the hypothesis that the disproportionate expansion of the coronal gyrus in somatosensory cortex of sea otters was also related to the high innervation investment of the mystacial vibrissal array, and that quantifying innervation investment was a good proxy for tactile sensitivity (George & Holliday, 2013). Recently, the hypothesis of sea otter vibrissae and paw sensitivity was confirmed by the behavioral research of Strobel, Sills, Tinker, and Reichmuth (2018). Despite the recency of sea otter return to the marine environment, their F-SC microstructure, innervation, and, presumably, function have converged with pinnipeds.…”
Section: Specialization and Convergence Of Tactile Sensation Using Vibrissae: Terrestrial To Semiaquatic To Aquatic Vibrissal Innervationmentioning
confidence: 70%
“…As comparative data become available, it will be important to identify metrics that can be used to assess performance across taxa and within sensory modalities. For example, recent data from sea otter paws show that the tactile sensitivity of their paws is greater than with their vibrissae (Strobel et al, 2018). The discrimination threshold with paws was ΔI = 0.27 mm, Weber fraction, k = 0.13 versus ΔI = 0.47 mm, Weber fraction k = 0.23 for vibrissae, where ΔI is the minimum discriminable difference between the standard and alternative targets.…”
Section: Behavioral Studies Of Touchmentioning
confidence: 97%
“…Textures consist of the microscale tactile features on the surfaces of objects, and provide important cues for sensory mediated behaviors in mammals ( Diamond, 2010 ). Texture discrimination via the skin has been described for various tactile sensing arrays in mammals including the fingertips in humans ( Lamb, 1983 ; Morley et al, 1983 ) and non-human primates (squirrel monkey, Hille et al, 2001 ; rhesus macaques, Connor et al, 1990 ; Connor and Johnson, 1992 ; Hollins and Bensmaia, 2007), the trunk in elephants ( Dehnhardt et al, 1997 ), and the forepaws of rats ( Bourgeon et al, 2004 ) and sea otters ( Strobel et al, 2018 ). In the whisker system, texture discrimination has previously been described most extensively for rats and mice ( Carvell and Simons, 1990 ; Arabzadeh et al, 2005 ; von Heimendahl et al, 2007 ; Wolfe et al, 2008 ; Diamond, 2010 ; Jadhav and Feldman, 2010 ; Pacchiarini et al, 2017 ), and in a few aquatic mammals, namely sea otters ( Strobel et al, 2018 ), harbor seals ( Dehnhardt et al, 1998 ), sea lions ( Dehnhardt, 1994 ; Dehnhardt and Dücker, 1996 ) and manatees ( Bachteler and Dehnhardt, 1999 ; Bauer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the skin forms a continuous sheet that is densely innervated, the whisker array consists of a discontinuous grid, with touch receptors concentrated at discrete locations. Despite these differences in the peripheral morphology, it has been shown that texture discrimination via the whiskers can be just as sensitive as that mediated by the skin on human fingertips ( Carvell and Simons, 1990 ; Bachteler and Dehnhardt, 1999 ; Diamond, 2010 ; Bauer et al, 2012 ; Strobel et al, 2018 ; O'Connor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%